Spiritual education and successful aging: A spiritual dialogue - Shih, Yi-Huang; Ku, Min-Sheng; Tseng, Shiuan-Yu; Chiang, Yu-Ming; Lin, Jason Cong (Edelweiss Applied Science and Technology, 2024)
Most people endeavor to prolong their lives and hope for a healthy old age, indicating that successful aging is extremely important for older adults. This article explored how spiritual education can enhance successful aging for older adults and develop a spiritual dialogue between them. The researchers used documentary analysis methods to analyze the successful aging methods for older adults. The successful aging methods outlined for older adults are as follows: (1) developing a sense of meaning and purpose; (2) making sense of life experiences; (3) emphasizing the importance of connection; (4) enhancing resilience; (5) enhancing life satisfaction; (6) encouraging a holistic view of well-being. The discussion in this article can expand approaches to successful aging methods for older adults.